2021
DOI: 10.21037/apm-20-2284
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of acute radiation-induced brain injury in a mouse model using anlotinib

Abstract: Background: With the development of radiological technologies, radiotherapy has been gradually widely used in the clinic to intracranial tumours and become standardised. However, the related central nervous system disorders are still the most obvious complications after radiotherapy. This study aims to quantify the effectiveness of anlotinib, a small molecule inhibitor of multiple receptor tyrosine kinases, in mitigating acute phase of radiation-induced brain injury (RBI) in a mouse model. Methods:The onset an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…8 In 2020 and 2021, oncologists suggested that anlotinib has intracranial activity and can control intracranial tumors. 12,20,21 The ALTER0303 study also showed that anlotinib can prolong PFS in lung cancer patients with BM. 12 Anlotinib normalizes the blood vessels in a metastatic tumor, adjusts the internal microenvironment of the tumor, restores the normal permeability of blood vessels, and acts synergistically with CRT to enhance radiosensitivity and reduce brain edema.…”
Section: Discussionmentioning
confidence: 99%
“…8 In 2020 and 2021, oncologists suggested that anlotinib has intracranial activity and can control intracranial tumors. 12,20,21 The ALTER0303 study also showed that anlotinib can prolong PFS in lung cancer patients with BM. 12 Anlotinib normalizes the blood vessels in a metastatic tumor, adjusts the internal microenvironment of the tumor, restores the normal permeability of blood vessels, and acts synergistically with CRT to enhance radiosensitivity and reduce brain edema.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, radiation triggers neuroinflammation and significantly increased the brain levels of the pro-inflammatory mediators IL-1β, IL-6, and NF-κB (Lee et al 2010 ; Yang et al 2017 ). Besides, the astrocytes proliferate and exhibit hypertrophic nuclei/cell bodies with an apparent elevation in the GFAP expression upon radiation injury (Greene-Schloesser et al 2012 ; Gao et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although, anlotinib failed to inhibit the development of demyelination, anlotinib treatment significantly attenuated the adverse effects of acute RBI in a dose-dependent manner by downregulating astrocyte activation, ameliorating cerebral hypoxia, and alleviating cerebral edema [14]. [14] study elucidated the palliative effect of anlotinib on acute RBI at the molecular level, which clearly…”
mentioning
confidence: 89%
“…Previously, GAO et al 's animal experiments on the mitigation of RBI by anlotinib were of great interest [14]. The authors evaluated changes in demyelination, glial cell activation, hypoxia, and microvascular permeability after anlotinib treatment by establishing a mouse model of RBI.…”
mentioning
confidence: 99%